Monte Carlo calculations on the gauge Potts model - Fanchiotti, Huner (1984)
The q-state gauge Potts model Pq in d-dimensions has been studied using Monte Carlo techniques. For d=2 no phase transitions were detected. The P2 model for d=3 shows a second order phase transition. On the other hand, all the d=3 (q≠2) and d=4 cases studied show first order phase transitions. In these cases, it was possible to estimate transition coupling parameters as well as latent heat. For selected cases, a study of the behavior of the Wilson loop factor was done.